40 years of New Zealand Sociology: The journal as a mirror of Sociology in Aotearoa New Zealand - Terruhn, Jessica; Uekusa, Shinya; Friedlander, Anna; Trotter-Simons, Bonnie-Estelle; Ran, Guanyu Jason (New Zealand Sociology, 2026)
New Zealand Sociology marks its 40th anniversary in 2026. This milestone provides us with a reason to celebrate the journal’s achievements as a platform for sociological scholarship in Aotearoa New Zealand. It also presents an opportunity to more closely examine its history. Analysing publication and author characteristics allows us to document trends and identify inequities for us to address these in the future. In this article, we share key findings from a document/publication trend analysis of all contributions published between 1986 and 2025, tracking contribution types, authorship and citations as well as thematic emphases of scholarship over time. Over the past four decades, research articles have become more prominent relative to other types of contributions. As has been common in the social sciences, authorship has been and remains highly individualised with nearly three quarters of all research articles sole-authored. Concerningly, author representation has been highly uneven. While gender representation has become more balanced over time, Indigenous and Pacific scholars remain underrepresented despite the journal’s stated aims to support scholarship of relevance to Indigenous and Pacific communities. Despite these imbalances, we note that gender is one of the three most prominent topics (alongside social theory and neoliberalism) and that citation patterns complicate prestige, gender and racial hierarchies. Our analysis shows that while average citation numbers are modest (compared to the Journal of Sociology and Kōtuitui), highly cited articles are often authored by women, Māori and Pacific scholars. Overall, we use these findings to prompt a wider discussion of NZS’s reach and future direction.